(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Stress is body’s way of response to inappropriate levels of pressure, any threat or demand probably in the areas of physical, chemical, financial, emotional or social levels. When the stress becomes overwhelming it can lead to mental and physical problems. Women of the middle age suffer the most due to change in hormonal levels, work pressure from home and office, lack of self-care and negligence of the same. Stress level is always seen higher in working women because of the added responsibilities given to her. The ability to overcome stress reduces with age. Stress over a period of time will throw a person off-balance and it has been linked to many health problems such as heart disease, high blood pressure and weakened immune function. Statistics prove that city life has stress as a package of life status. The significance of this study is to identify the psycho-social issues related to stress in middle-aged working women at the city level, the related illness and diseases that could be acquired as a result of the stress and its importance to create an awareness of stress-busters. Psycho-social interventions have proven useful for treating stress related disorders.